China’s ‘Going Out’ Strategy in Southeast Asia: Case Studies of the Automobile and Electronics Sector - Lim, Guanie Cia Lit (2017)
In view of China’s “going out” programme, this article argues that mainland Chinese firms have not made significant breakthroughs in the Southeast Asian automobile sector, primarily because of a competitive and still consolidating marketplace, various national regulations of Southeast Asian countries, and the need to dovetail their own corporate goals with those of their Southeast Asian partners. Meanwhile, mainland Chinese firms have made major advances in the Southeast Asian electronics sector by offering low prices and high-quality products and services. In addition, they also collaborate with marketing firms that possess intimate knowledge of the marketplace.